Promoting Models of Moderate Islam-based Education: Insight from Indonesia and Australia - Mustakim, Zaenal (Hikmatuna : Journal for Integrative Islamic Studies, 2020)
In response to the need for enacting Islamic education to tackle radicalism and violent extremism (RVE), the present study aims to explore the models of moderate Islam-based education in Indonesia and Australia and to explain the challenges in promoting moderate Islam in both countries. Grounded in an exploratory case study, data were garnered through in-depth interviews and observation. Findings of this study expose that firstly, the Nahdlatul Ulama (NU) chairmen in both Central Java, Indonesia and Melbourne, Australia portrayed the same views on moderate Islam; it was religiously and ideologically situated between two radical and extremist groups, i.e., the fundamentalist group and the liberal one. Secondly, the model of moderate Islam-based education depicted by the NU chairpersons in Central Java, Indonesia employed two approaches, namely: formal madrasas/schools and non-formal education, and the strategies performed in the formal education proposed a design of moderate Islam value-based learning. Meanwhile, the model of moderate Islam-based education in Melbourne, Australia applied non-formal education. Lastly, this study also reveals several challenges encountered in fostering moderate Islam to confront the problem of RVE emerged in the sector of Islamic education in Indonesia and Australia.